Concejil Sigillography: the seal of the city council of Puerto Real under the jurisdiction of Jerez de la Frontera (1517) - Jiménez López de Eguileta, Javier E. (Documenta & Instrumenta - Documenta et Instrumenta, 2022)
The discovery of a seal of the city council of Puerto Real from 1517, that is, during the period wich the town was legally subjected to Jerez de la Frontera, has allowed to develop its sigillographic study and a short contribution of some historical notes about the political relationship between both municipalities.
Keywords: Sigillography; city council seal; Puerto Real; Jerez de la Frontera; 16th century